An H-Based A-$φ$ Method with a Nonmatching Grid for Eddy Current Problem with Discontinuous Coefficients (Journal of Computational Mathematics, 2021)
In this paper, we investigate the finite element A-$φ$ method to approximate the eddy current equations with discontinuous coefficients in general three-dimensional Lipschitz polyhedral eddy current region. Nonmatching finite element meshes on the interface are considered and optimal error estimates are obtained.